Improving student expectations of learning in a problem-based environment. - Rovers, Sanne F.E.; Clarebout, Geraldine; Savelberg, Hans H.C.M.; van Merriënboer, Jeroen J.G. (Computers in Human Behavior, 2018)
Despite the continuing popularity of problem-based learning (PBL) approaches in higher education worldwide, concerns have been raised regarding a decrease in effectiveness. Unrealistic expectations of students about the nature of learning in a PBL setting may lead to ineffective use of self-regulated learning strategies, in turn leading to suboptimal learning during self-study. In this study, we tested the effects of a workshop aimed at aligning students' perceptions and expectations of their learning environment to those of the university as expressed in faculty training programs. First-year PBL medical students were randomly assigned to either a control condition ( n  = 26) or a contrast (workshop) condition ( n  = 19), designed to enable them to compare and contrast their expectations to those of the university. Results showed no significant differences between conditions in students' reported use of SRL strategies, but indicated a differential development in students' intentions to take responsibility for their own learning, with students in the contrast condition reporting an increase in these intentions as a result of the intervention. The intervention did not have a differential effect for students with different pretest scores. We discuss how optimization of the PBL environment can inform the design of online, computer-based support tools.